Effect of ovarian growth factors on ultra-structural maturation in frozen human immature oocytes after in vitro maturation: a comparative study - Hakimeh Akbari; Masoud Mohammadi (BMC, 2022)
Plain Language Summary In artificial reproductive technique (ART), nearly 20% of human oocytes are immature in the germinal vesicle (GV) phase. Consequently, the best method for reserving them is cryopreserving GV oocytes, and in vitro maturation (IVM) is recommended. This study was a comparative laboratory study carried out in 2018 at Afzalipur Infertility Center in Kerman. 170 fresh and 198 vitrified GV oocytes were cultured within three IVM mediums; α-mem as the control medium, α-mem supplemented with human bone marrow mesenchymal stem cells (BM-MSCs), and α-mem supplemented with ovarian growth factors (O.F). After 48 h, the maturation rate and morphological features of IVM oocytes were evaluated. For the ultrastructure study, 10 IVM oocytes from each medium were compared with 10 fresh in vivo oocytes cancelled from ART. The survival rate of vitrified GV oocytes after thawing was 88.88%. The oocyte maturation rate was reduced in vIVM compared to the fIVM group (76.33% vs. 77.95%); the highest oocyte maturation rate in the O.F fIVM and lowest in α-mem vIVM (82.35% vs. 71.42%). The lowest number of cortical granules was observed in α-mem vIVM, but the greatest presence of M-SER aggregates was in O.F fIVM. In vIVM oocytes, the oolemma contained irregular little microvillus organization. The O.F mediums have shown the highest maturation with defending the oocyte ultra-structural conservation.